Viability of Lacticaseibacillus paracasei in ultrafiltered white brined cheese packaged in modified atmosphere and flexible multilayer films - Heidarvand, Maryam (Array, 2021)
In this study, two packaging materials, modified polypropylene (MPP) and polyethylene terephthalate/aluminum/ low-density polyethylene (PETFA-Al-LDPE) were studied under various atmospheric conditions: 100 % CO2, 70 % N2 - 30 % CO2, 80 % N2 - 20 % CO2 for packing probiotic ultrafiltered (UF) white brined cheese. pH, titratable acidity, moisture content, Lacticaseibacillus paracasei viability and overall acceptability were monitored within a 12- week period. The control samples were packaged in atmospheric air. Results revealed that samples packaged in PETFA-Al-LDPE with the combination of 70 % N2 - 30 % CO2 had the lowest pH, highest acidity and moisture content. The viability of Lacticaseibacillus paracasei was reported to be 4*106 CFU/g within 12 weeks. The highest and lowest overall acceptability was for the cheese packaged in 70% N2 - 30 % CO2 and the control sample, respectively.